Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan, Leverage, Umur Obligasi dan Reputasi KAP Terhadap Peringkat Obligasi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015 - Prastika, Gilang Elly; , Dr. Fatchan Achyani, S.E., M.Si (2017)
Bond rating is something that should be considered for investors and issuers before making a decision on bond investment. Bond rating provides an informative statement and signals about the probability of failur of a company's debt. The purpose of this research is to providing emipical evidance on any factors that possibly affect bond rating. This study examines the factors which consist of profitability, , liquidity, size, leverage, maturity and KAP reputation of the bond rating. The population used in this study focused on manufacturing companies rated by PT. PEFINDO and listed in Indonesia Stock Exchange 2013-2015. The number of samples collected as many 50 companies. Outliers data as many as 11 companies, so that the samples to 39 companies. Research hypothesis tested by Multiple Linear Regression with sample collection methods using purposive sampling. The result of this research: 1) profitability, size, and KAP reputation has affect to the bond rating, and 2) likuidity, leverage, and maturity has no affect to the bond rating. Keywords: Bond rating, Profitability, Likuidity, Size, Leverage, Maturity, KAP Reputation, and Multiple Linear Regression.